2019
DOI: 10.3390/coatings9030172
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesoporous Silica Nanoparticles on Glycerol-Plasticized Anionic and Cationic Polysaccharide Edible Films

Abstract: This study describes the production of reinforced polysaccharide (PS)-based films, by adding mesoporous silica nanoparticles (MSNs), to either pectin (PEC) or chitosan (CH) film forming solutions, either containing glycerol (GLY) as a plasticizer, or not. Film characterization demonstrated that MSNs and GLY were able to significantly increase the plasticity of both PS-based biomaterials and that the interactions between PSs and nanoparticles were mainly due to hydrogen bonds. Moreover, MSN-containing films wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
(36 reference statements)
1
19
0
Order By: Relevance
“…This result was obtained also by Fernandez-Bats et al [14], that have studied protein films, concluding that the MSN addition gives rise to materials less permeable to gases and WV. The obtained results could be explained taking into account the structure of such films studied in a recent work [55]. In fact, in this study it has been reported that MSN-containing PEC-based films possess a more compact and homogeneous structure in comparison to the film prepared without any MSNs [55].…”
Section: Co 2 O 2 and Water Vapor (Wv) Permeabilitymentioning
confidence: 57%
See 2 more Smart Citations
“…This result was obtained also by Fernandez-Bats et al [14], that have studied protein films, concluding that the MSN addition gives rise to materials less permeable to gases and WV. The obtained results could be explained taking into account the structure of such films studied in a recent work [55]. In fact, in this study it has been reported that MSN-containing PEC-based films possess a more compact and homogeneous structure in comparison to the film prepared without any MSNs [55].…”
Section: Co 2 O 2 and Water Vapor (Wv) Permeabilitymentioning
confidence: 57%
“…In particular, the PEC-based films containing MSNs or GLY showed a higher value of EB, and a reduced YM, while a more marked effect on these parameters was obtained by adding both MSNs and GLY. At the same time, the concurrent presence of MSNs and GLY significantly reduced the tensile strength of the PEC-based films [55].…”
Section: Mechanical Propertiesmentioning
confidence: 89%
See 1 more Smart Citation
“…Taking into account the fact that the total amount of plastic use currently exceeds 200 million tons annually, with an increase of about 5% per year, it is essential that alternative materials be used instead of conventional, non-recyclable and/or non-biodegradable packaging, thus solving many ecological problems. A relevant example is the Great Pacific Garbage Patch-in the central North Pacific, where plastic waste has formed an artificial island of about one million km 2 , the result of marine pollution [1]. At present, tons of plastic packaging are discarded into nature, making the waste problem a bigger one year after year.…”
Section: Introductionmentioning
confidence: 99%
“…Recycling the packaging would be impractical and economically inconvenient, because of the residues from food products and other biological substances. Under the circumstances, the use of biodegradable and eco-friendly biopolymer-based packaging represents the best candidate for reducing the huge amount of conventional plastics, being "bioplastics, manufactured exclusively with natural polymers, which are able to be fully recycled into the environment, into a short time, following their utilization as packaging materials" [2].…”
Section: Introductionmentioning
confidence: 99%